The associations between renal disease severity and exposure to organophosphate flame retardants in patients with chronic kidney disease. (December 2022) - Tsai, Kai-Fan; Cheng, Fu-Jen; Huang, Wan-Ting; Kung, Chia-Te; Lee, Chien-Te; Cheng, Ben-Chung; Chen, Jin-Bor; Li, Shau-Hsuan; Wang, Chin-Chou; Wang, Liang-Jen; Ou, Yu-Che; Lee, Wen-Chin
Graphical abstract: Highlights: Organophosphate flame retardant exposure is common in chronic kidney disease. Urinary organophosphate flame retardant level is associated with renal impairment. Proteinuria could be impacted by organophosphate flame retardant exposure. Organophosphate flame retardant exposure might be altered by age and diet. Abstract: Organophosphate flame retardants (OPFRs) are emerging and widespread environmental pollutants with potential health hazards, including nephrotoxicity. However, the exposure patterns and nephrotoxic potential of OPFRs are yet to be investigated in patients with chronic kidney disease (CKD). We conducted a cross-sectional study involving 166 patients with CKD stratified by estimated glomerular filtration rate (eGFR) and severity of proteinuria. The urinary concentrations of 10 OPFR compounds were measured to evaluate the exposure patterns. Clinical and urinary OPFR profiles were compared among subgroups to identify whether the OPFR compounds were independently correlated with eGFR and proteinuria. Additionally, lifestyle factors were compared among subgroups stratified by median concentrations of urinary OPFR compounds associated with renal disease severity. This study revealed universal exposure to OPFRs in the CKD population, with an overall urinary detection rate of 98.80 %. Furthermore, after adjusting for covariates, the urinary concentration of bis(2-chloroethyl) phosphate (BCEP) was identified as an independent predictor of lower eGFR (low vs high eGFR, odds ratio (OR) (95 % confidence interval (CI)), 1.761 (1.032–3.005) per log μg/g creatinine, p = 0.038), and the urinary concentration of bis(2-butoxyethyl) phosphate (BBOEP) was independently correlated with overt proteinuria in CKD patients (with vs without overt proteinuria, OR (95 % CI), 1.813 (1.065–3.086) per log μg/g creatinine, p = 0.028). Moreover, frequent seafood consumption was negatively correlated with urinary BCEP concentration (high vs low BCEP, OR (95 % CI), 0.455 (0.228–0.908), p = 0.025), and age was inversely associated with urinary BBOEP concentration (high vs low BBOEP, OR (95 % CI), 0.968 (0.937–0.999) per year, p = 0.048). In conclusion, our investigation highlights the extensive exposure to OPFRs and the independent association between renal disease severity and urinary BCEP/BBOEP concentrations in the CKD population, indicating the nephrotoxic potential of these pollutants.